MENGAMBIL MANFAAT MEDIA SOSIAL DALAM PENGEMBANGAN LAYANAN - Widada, Cahyana Kumbul (Association of Indonesian Library and Information Professionals, 2018)
Information technology has brought changes in all aspects of life in today's modern world. The Internet is becoming more popular and familiar as a source of information. Social media is a medium on the internet that allows users to represent themselves as well as interact, cooperate, share, communicate with other users and form a virtual social bond. The type of social media with all its characteristics brings a positive influence in building the service model. In research at Library of Muhammadiyah University of Surakarta (UMS) the users of social media Facebook (29%), Youtube (22%), Instagram (21%), Twitter (17%), Blog (7%), and wiki (4%). Facebook is the most popular of social media, allowing it to be developed as a means of meeting and online discussions that interact with each other.